Athletes as Abusers and Victims: The Impact of Gender Integration and Institutional Betrayal on Gender-Based Violence in “Other” U.S. Sports - Smith, Earl (Violence against women, 2025)
Gender-based violence (GBV) within major collegiate (NCAA) sports, the National Football League (NFL), the National Basketball Association (NBA), and Major League Baseball (MLB) has been well document. However, gender-based violence in other sports is understudied. Analysis of the Gender-Based Violence in Sport database reveals six key differences between gender-based violence in football, baseball, and basketball as compared to other sports. Utilizing the framework of intersectional feminism, we theorize the lower rates of athlete-perpetrated gender-based violence, the disproportionate role that trainers, doctors, staff, and coaches play in its perpetration, and the higher rates of athlete victimization in these other sports.